(untitled) (Journal of Medical & Health Sciences Review, 2025)
Universal Health Coverage (UHC) is a fundamental policy initiative that ensures access to quality healthcare services without financial hardship. This study examines the economic impact of Universal Health Coverage (UHC) on Pakistan’s economic growth from 2010 to 2023. By analyzing healthcare expenditures, labor productivity, and GDP growth, the research highlights how improved healthcare access contributes to economic stability and workforce efficiency. The study employs a mixed-methods approach, utilizing quantitative data from the World Bank, World Health Organization, and Pakistan Bureau of Statistics, along with qualitative policy analysis. The findings indicate that increased healthcare spending positively influences labor force participation, reduces disease burden, and enhances productivity, ultimately driving economic growth. However, challenges such as inadequate funding, governance issues, and infrastructure constraints hinder full Universal Health Coverage (UHC) implementation. The study concludes with policy recommendations emphasizing public-private partnerships, enhanced government investment in healthcare, and technology-driven solutions like telemedicine. Furthermore, ensuring Universal Health Coverage (UHC) in Pakistan is not just a social obligation but a strategic economic necessity for long-term sustainable growth.